2020
DOI: 10.1016/j.bbadis.2020.165823
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced immune system response: Anti-inflammatory status on peripheral and central organs

Abstract: A wide array of molecular pathways has been investigated during the past decade in order to understand the mechanisms by which the practice of physical exercise promotes neuroprotection and reduces the risk of developing communicable and non-communicable chronic diseases. While a single session of physical exercise may represent a challenge for cell homeostasis, repeated physical exercise sessions will improve immunosurveillance and immunocompetence. Additionally, immune cells from the central nervous system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
174
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(196 citation statements)
references
References 206 publications
5
174
0
17
Order By: Relevance
“…Im Rahmen von präventiven Maßnahmen sind z. B. immunmodulierende und antiinflammatorische Effekte einer gesunden Lebensweise bereits früh im Pandemiegeschehen diskutiert worden [ 44 , 45 ]. Bisher liegen aber noch keine epidemiologischen Daten oder Interventionsstudien vor, die den Zusammenhang zwischen Ernährung, Bewegungsverhalten und COVID-19 untersuchten.…”
Section: Prävention Und Therapieempfehlungen Für Covid-19unclassified
“…Im Rahmen von präventiven Maßnahmen sind z. B. immunmodulierende und antiinflammatorische Effekte einer gesunden Lebensweise bereits früh im Pandemiegeschehen diskutiert worden [ 44 , 45 ]. Bisher liegen aber noch keine epidemiologischen Daten oder Interventionsstudien vor, die den Zusammenhang zwischen Ernährung, Bewegungsverhalten und COVID-19 untersuchten.…”
Section: Prävention Und Therapieempfehlungen Für Covid-19unclassified
“…Araujo et al [ 16 ] suggested that physical training induces adaptations to the stress mediated by an immune response, resulting by changes in the cytokine profile. However, pro-inflammatory cytokines (including IL-6, TNF-alpha and IL-17AA) may be preferentially upregulated during acute exercise, while chronically prolonged physical activity may promote an anti-inflammatory status presumably associated with IL-10 secretion [ 3 , 4 , 14 , 17 , 18 , 19 ]. Furthermore, Heisterberg et al [ 20 ] have shown that variations of haemoglobin and haematocrit were related to the amount of aerobic and anaerobic training, strength training and the number of matches per week in professional soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that exercise is closely related to the immune ability of the body. [ 7 ] Regular exercise can significantly improve the immune ability of the body and reduce the incidence of infectious diseases, [ 8 ] while long-term high-intensity exercise or lack of exercise is an important cause of immune decline. [ 9 , 10 ] Bernardi and Simpson found that regular moderate intensity training can significantly improve the immune ability of the body and effectively reduce the incidence of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%